2019
DOI: 10.1111/jace.16837
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of sodium silicate glasses from reactive force field‐based molecular dynamics simulations

Abstract: Atomistic computer simulations can provide insights into silicate glass‐environment interactions with the recent development of reactive potentials. However, the accuracy of generated glass structures with these potential was usually not fully examined. In this paper, the capability of the reactive force field (ReaxFF) to describe the short and medium range structure features of sodium silicate glasses in molecular dynamics simulations is investigated by comparing a widely used partial charge pairwise potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Thus, it can be concluded that the MD simulation results from the Teter potential would be inadequate to describe the structural features of glass that are relevant to the vibrational spectra. It is known that the partial charge pairwise Teter potential can generate reasonable short and medium range structures that are comparable to experimental data for sodium silicate glasses and, as a result, it has been widely used in the structural studies of silicate glasses . However, the fixed charge potential does not take into the ion polarization effect, which plays an important role in the vibrational spectra of the glass networks.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, it can be concluded that the MD simulation results from the Teter potential would be inadequate to describe the structural features of glass that are relevant to the vibrational spectra. It is known that the partial charge pairwise Teter potential can generate reasonable short and medium range structures that are comparable to experimental data for sodium silicate glasses and, as a result, it has been widely used in the structural studies of silicate glasses . However, the fixed charge potential does not take into the ion polarization effect, which plays an important role in the vibrational spectra of the glass networks.…”
Section: Resultsmentioning
confidence: 97%
“…It is known that the partial charge pairwise Teter potential can generate reasonable short and medium range structures that are comparable to experimental data for sodium silicate glasses and, as a result, it has been widely used in the structural studies of silicate glasses. 54,[73][74][75][76] However, the fixed charge potential does not take into the ion polarization effect, which plays an important role in the vibrational spectra of the glass networks. It has been shown previously that including polarization can significantly improve the peak position and relative intensity of silica glass.…”
Section: Choosing Proper Potential For MD Simulationsmentioning
confidence: 99%
“…A more detailed atomic structural analysis on the ReaxFF modeling of sodium silicate glass can also be found in Ref. [28].…”
Section: Methodsmentioning
confidence: 99%
“…F I G U R E 1 ReaxFF-MD simulation of a sodium silicate glass surface rubbed with an amorphous silica (a-SiO 2 ) slab A more detailed atomic structural analysis on the ReaxFF modeling of sodium silicate glass can also be found in Ref. [28]. Figure 1 provides an overview of the MD simulation steps that we employed for the mechanochemical reaction at the contacting interface.…”
Section: Reaxff-md Simulationsmentioning
confidence: 99%
“…The presence of Al 2 O 3 has been widely believed to be critical because it can significantly improve the chemical durability, mechanical properties, and various other thermodynamics behaviors 7‐10 . The intrinsic correlation between various properties and glass structure for the system in different composition space has been extensively studied over the past few decades, both by experiments 11‐16 and simulations 10,17,18 . One of the hottest research interests is the local aluminum and oxygen environment as glass composition with respect to Al/Na ratio ( R Al/Na ) transitions from peralkaline ( R Al/Na < 1) to peraluminous ( R Al/Na > 1) because it is believed to be strongly correlated to many non‐monotonic composition‐property relationships observed in the system.…”
Section: Introductionmentioning
confidence: 99%